The normativity of nature in Aristotle and St. Thomas. Physis and natural just in classical philosophy - Aguirre, Sebastián Contreras (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This paper analyses the concept of «physis» that the classical philosophy —specifically Aristotle and Aquinas— exposes about the problem of «natural just». In this sense, the author pretends a review of the main theoretical and metaphysical implications of the existence of a normative nature in legal philosophy and ethics.
Keywords: nature; natural just; Aristotle; Aquinas; classical philosophy